2016
DOI: 10.1155/2016/6372181
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Trifascicular Block in Steinert’s Disease: Is It Too Soon for a Pacemaker?

Abstract: We report a case of a 62-year-old male with Steinert's disease who presented with progressive intermittent episodes of lightheadedness five years after he was diagnosed with the disease. On evaluation, he developed a new onset trifascicular block (first degree atrioventricular block, new onset right bundle branch block, and left anterior fascicular block). A dual chamber pacemaker was inserted and lightheadedness improved significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…With interest we read the article by Lasam et al about a 62yo male with genetically confirmed myotonic dystrophy type I (MD1) who developed a trifascicular block (AV-block I, left anterior hemiblock, and right bundle branch block) which manifested clinically as lightheadedness [ 1 ]. After implantation of a dual chamber pacemaker, lightheadedness improved.…”
mentioning
confidence: 99%
“…With interest we read the article by Lasam et al about a 62yo male with genetically confirmed myotonic dystrophy type I (MD1) who developed a trifascicular block (AV-block I, left anterior hemiblock, and right bundle branch block) which manifested clinically as lightheadedness [ 1 ]. After implantation of a dual chamber pacemaker, lightheadedness improved.…”
mentioning
confidence: 99%
“…Steinert's disease or myotonic dystrophy type 1 (DM1) has been associated with the presence of an abnormal expansion of a CTG trinucleotide repeat on chromosome 19q13.3 [ 2 ] and has been correlated with cardiac involvement [ 3 ]. On our clinical vignette entitled “Symptomatic Trifascicular Block in Steinert's Disease: Is It Too Soon for a Pacemaker?” [ 4 ], we tried to retrieve the specific genetic code and expansion repeats for our patient but to no avail. The patient's neurologist retired a decade ago and we were unable to get the specific information about the genetics of our patient's disease.…”
mentioning
confidence: 99%